1999
DOI: 10.3109/08860229909094156
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Bioflavonoid Proanthocyanidin-BP1 in Glycerol-Induced Acute Renal Failure in the Rat: Renal Stereological Study

Abstract: Renal ischemia as well as oxygen metabolites play an important role in renal injury during myoglobinuric acute renal failure (ARF). On the other hand, flavonoids, a diverse group of constituents naturally occurring in plants, have a strong antioxidative activity, and have been implicated in vascular relaxation. In this study the protective effect of a new bioflavonoid proanthocyanidin-BP1 (BP1), extracted from seeds of grapes, was evaluated in glycerol-induced ARF in rats. Stereological methods were used to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Also, a renoprotective effect by the wine bioflavonoid proanthocyanidin-BP1 was reported in a study examining the same glycerol-induced rhabdomyolysis animal model used in the present experiments [20]. It is unlikely that extrarenal effects of the treatments and of rhabdomyolysis contributed to the observed renal protection since systemic parameters other than FRAP, such as haemodynamics and uricaemia, were not different between the groups at basal conditions or after glycerol injection.…”
Section: Discussionmentioning
confidence: 66%
“…Also, a renoprotective effect by the wine bioflavonoid proanthocyanidin-BP1 was reported in a study examining the same glycerol-induced rhabdomyolysis animal model used in the present experiments [20]. It is unlikely that extrarenal effects of the treatments and of rhabdomyolysis contributed to the observed renal protection since systemic parameters other than FRAP, such as haemodynamics and uricaemia, were not different between the groups at basal conditions or after glycerol injection.…”
Section: Discussionmentioning
confidence: 66%
“…Several mechanisms have been proposed for the protective effect of silybin. For instance, as an antioxidant, it may scavenge ROS via chelating ferric ions . As an antiinflammatory, it may decrease cyclooxygenase‐2 expression by interfering with nuclear factor κ‐ß or degrade tumor necrosis factor‐α by increasing expression of dipeptidylpeptidase IV in renal tubular cells .…”
Section: Discussionmentioning
confidence: 99%
“…Azuki beans are known to contain polyphenols such as proanthocyanidins with remarkable radical scavenging activities in vitro [1,2]. Proanthocyanidins have some preventive effects against oxidative damage associated with a variety of diseases, including inflammation, cardiovascular diseases, atherosclerosis and diabetes [4][5][6]. However, little is known about whether a diet of seed coats of the azuki bean has beneficial effects on diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, proanthocyanidins are known to be natural antioxidants that possess protective properties against oxidative stress. For example, grape seed proanthocyanidins extract has been reported to have beneficial effects on inflammation [4][5][6], cancer [7,8] and diabetes [9,10]. Recently, we demonstrated that polyphenol-containing azuki bean seed coats attenuated the increase of infiltrating macrophages and tubulointerstitial fibrosis in kidneys of rats induced by cisplatin, which has been used as a chemotherapeutic agent against malignant carcinoma [11].…”
Section: Introductionmentioning
confidence: 97%